Empowering Hotel Staff through Task-Based Language Teaching: A Case Study in Room Service and Reservations - M Bambang Purwanto; Marsinah Marsinah; Nozylianty Nozylianty; Aisyah Aisyah (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
In the hospitality industry, English communication skills are essential in providing quality services, especially for interactions with international guests. However, many employees need help mastering vocabulary and speaking fluency, especially in work tasks such as reservations and room service. This study aims to evaluate the effectiveness of task-based language teaching (TBLT) in improving the communication skills of hotel employees and identify obstacles and solutions to its implementation. This study uses a qualitative approach with a 20 Grand Duta Syariah Palembang hotel employees' case study. The results showed a significant improvement in vocabulary and speaking skills and a positive response to the relevance of the TBLT method. Simulation-based strategies and gradual training overcame obstacles in task design and technology application. This research offers a new approach to developing language training in the hospitality industry by integrating authentic tasks into training. In conclusion, TBLT is practical and applicable to professional training needs.